2015
DOI: 10.1016/j.amjcard.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Atherectomy for Treating De Novo Severely Calcified Coronary Narrowing (1-Year Results from the Pivotal ORBIT II Trial)

Abstract: Percutaneous coronary intervention of severely calcified lesions has historically been associated with major adverse cardiac event (MACE) rates as high as 30%. In the ORBIT II (Evaluate the Safety and Efficacy of OAS in Treating Severely Calcified Coronary Lesions) trial, treatment of de novo severely calcified lesions with the Diamondback 360° Coronary Orbital Atherectomy System (OAS) resulted in low rates of procedural and 30-day adverse ischemic events. The long-term results from this trial have not been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 29 publications
(11 reference statements)
2
32
0
Order By: Relevance
“…Finally, it is important to mention that the current study reports a higher rate of TLR in comparison to data of two recently published large‐scale analyses in the field of coronary calcification, the 1‐year results from the ORBIT II trial and the pooled analysis of the HORIZONS‐AMI and ACUITY studies on ischemic outcomes after coronary intervention of calcified vessels . These differences in outcome could be partially explained by differing treatment strategies and follow‐up procedures among the three studies.…”
Section: Discussionmentioning
confidence: 44%
“…Finally, it is important to mention that the current study reports a higher rate of TLR in comparison to data of two recently published large‐scale analyses in the field of coronary calcification, the 1‐year results from the ORBIT II trial and the pooled analysis of the HORIZONS‐AMI and ACUITY studies on ischemic outcomes after coronary intervention of calcified vessels . These differences in outcome could be partially explained by differing treatment strategies and follow‐up procedures among the three studies.…”
Section: Discussionmentioning
confidence: 44%
“…Similarly, abrupt closure occurred in Table 4. Univariate analysis of factors influencing the incidence of major adverse cardiac events (MACE) and major cardiac and cerebrovascular events (MACCE) after rotational atherectomy procedure CABG -coronary artery bypass grafting; CI -confidence interval; COPD -chronic obstructive pulmonary disease; DAPT -dual antiplatelet therapy; GFR -glomerular filtration rate; HR -hazard ratio; IVUs -intravascular ultrasound; LVEF -left ventricular ejection fraction; OACoral anticoagulation; PCI -percutaneous coronary intervention; RCA -right coronary artery; TIA -transient ischaemic attack 0.9% of individuals after the use of OA, and in 1.8%, after the procedure, compared with rates from 1% to 4% from other studies that reported abrupt closure during RA [11,12]. Perforations occurred in 0.9% of patients after the use of OA and in 1.8% after the procedure, compared with 0.4% to 2.5% in RA studies reporting on this complication [15].…”
Section: Discussionmentioning
confidence: 90%
“…Perforation rates of 0% to 1.5% have been reported with high-speed RA, and they differ based on technique [15]. The ORBIT II trial had among the lowest rates of this complication [11]. Similarly, abrupt closure occurred in Table 4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…OA, a newcomer to coronary interventions, was first introduced in coronary arteries in 2013 in the ORBIT I trial [23]. Recent studies showed promising results of OA in hospital as well as in long-term follow-up [24,25]. On the other hand, manufacturers of both devices included thrombus-containing lesions as a contraindication to the procedure.…”
Section: Discussionmentioning
confidence: 99%